Precipitous Birth - Jennifer Yee; Andrew King (eScholarship Publishing, University of California, 2017)
Audience: This scenario was developed to educate emergency medicine residents on the management of a precipitous birth in the emergency department (ED). The case is also appropriate for teaching of medical students and advanced practice providers, as well as reviewing the principles of crisis resource management, teamwork, and communication. Introduction: Patients with precipitous birth require providers to manage two patients simultaneously with limited time and resources. Crisis resource management skills will be tested once baby is delivered, and the neonate will require assessment for potential neonatal resuscitation. Objectives: At the conclusion of the simulation session, learners will be able to manage women who have precipitous deliveries, as well as perform neonatal assessment and management. Method: This session was conducted using high-fidelity simulation, followed by a debriefing session and lecture on precipitous birth management and neonatal evaluation.